Evidence of Oxidative Shielding of Offspring in a Wild Mammal - Vitikainen, Emma I. K.; Cant, Michael A.; Sanderson, Jennifer L.; Mitchell, Christopher; Nichols, Hazel J.; Marshall, Harry H.; Thompson, Faye J.; Gilchrist, Jason S.; Hodge, Sarah J.; Johnstone, Rufus A.; Blount, Jonathan D. (Frontiers in Ecology and Evolution, 2016)
Oxidative damage has been proposed as a potential mechanism underlying a life history tradeoff between survival and reproduction. However, evidence that reproduction is associated with increased oxidative damage is equivocal, and some studies have found that breeding females exhibit reduced, rather than elevated, levels of oxidative damage compared to equivalent non-breeders. Recently it was hypothesized that oxidative damage could have negative impacts on developing offspring, and that mothers might down-regulate oxidative damage during reproduction to shield their offspring from such damage. We tested this hypothesis through a longitudinal study of adult survival, reproduction, and oxidative damage in wild banded mongooses (Mungos mungo) in Uganda. High levels of oxidative damage as measured by malondialdehyde (MDA) were associated with reduced survival in both sexes. Levels of protein carbonyls were not linked to survival. Mothers showed reduced levels of MDA during pregnancy, and individuals with higher MDA levels gestated fewer offspring and had lower pup survival. These results suggest that maternal oxidative damage has transgenerational costs, and are consistent with the idea that mothers may attempt to shield their offspring from particularly harmful types of oxidative damage during pregnancy. We suggest that further advance in understanding of life history variation could benefit from theoretical and empirical exploration of the potential transgenerational costs of reproduction.